Resilience, Parents, Children wi Resilience in Parents with Children with Special Needs in Special Schools: Resilience in Parents with Children with Special Needs in Special Schools - Khotimah, Husnul (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2024)
The birth of a child is a highly anticipated moment for married couples, but not all children are born it typical health, with some being Children with Special Need (ABK). This research aims to explore the resilience of parents who have children with special needs in special schools (SLB) in East Lombok. Using a qualitative case study approach, data were collected through observation, interviews, and documentation from three participants selected by purposive sampling. The study found that parents demonstrated varying levels of resilience. One parent reached the “Thriving” stage, showing strong resilience, while the other two were in the “Recovery” stage, meaning they could adapt but still faced emotional challenges. All three parents showed resilience through the I am, I Have, and I Can factors, and believed their experiences were part of God’s destiny.